The Schooling of Forced Immigrant Afghan Youths in Iran: A Study of the Factors Leading to Exclusion - Ghasemi-Tafreshi, Samira; Lafortune, Gina (Comparative and International Education / Éducation comparée et internationale, 2023)
This article presents the results of a qualitative study which aims to better understand the educational paths of young Afghans in Iran. We conducted individual interviews with five child-parent pairs living in Tehran. The participants were invited to describe their families’ migratory experiences and the youths’ academic backgrounds. The interview data revealed that different intertwining factors led to the exclusion of the youths from school. These factors were tied to immigration policies and the youths’ social, familial, and educational environments. The results also showed that the youths were resilient; despite the many obstacles they had faced, they continued their efforts to achieve their academic and professional goals. This research highlights the challenges of welcoming and integrating young refugees in a non-Western context and contributes to the advancement of knowledge about the phenomenon of school exclusion in developing countries.